Homeownership and Housing Displacement after Hurricane Katrina among Low-Income African-American Mothers in New Orleans - Fussell, Elizabeth (Social science quarterly, 2014)
OBJECTIVE: We evaluate the effect of pre-Katrina housing tenure and post-disaster financial resources on the odds of housing displacement after Hurricane Katrina for a sample of low-income African-American mothers